Learning from mixed OR method practice: The NINES case study. (June 2017) - Howick, Susan; Ackermann, Fran; Walls, Lesley; Quigley, John; Houghton, Tom
Abstract: Despite continued interest in the use of mixed OR/MS methods, limited attention has been paid in the literature to generic lessons that could be gained from mixing methods in practice . Many organisational problems demand the use of a mixed method approach and thus recognising and sharing lessons could prove beneficial to both practitioners and researchers. This paper reports on an in-depth evaluation of a case study involving risk identification and quantification of the Northern Isles New Energy Solutions (NINES) project which sought to trial and plan a new energy system. The intervention involved a mixed method approach and client feedback on the efficacy of the approach was sought. The evaluation reported in this paper is carried out using a set of themes taken from the literature and seeks to highlight transferable lessons. The set of lessons that emerge are presented along with their implications for both general OR modelling practice and the specific situation of mixing OR/MS methods. The paper concludes by discussing the implications of the work and directions for future work which will be of interest to both practitioners and researchers interested in mixed method OR/MS work. Highlights: In-depth evaluation of an OR/MS mixed method intervention. Case study involving the NINES project – a large state of the art energy project. A set of generic lessons to benefit practitioners and researchers who mix methods. Lessons for design and implementation of intervention, modelling team, client value.